Lupus in Latin-American patients: lessons from the GLADEL cohort. (May 2015) - Pons-Estel, G J; Catoggio, L J; Cardiel, M H; Bonfa, E; Caeiro, F; Sato, E; Massardo, L; Molina-Restrepo, J F; Toledano, M Guibert; Barile-Fabris, L A; Amigo, M C; Acevedo-Vásquez, E M; et al.
The need for comprehensive published epidemiologic and clinical data from Latin American systemic lupus erythematosus (SLE) patients motivated the late Dr Alarcón-Segovia and other Latin American professionals taking care of these patients to spearhead the creation of theG rupoL atinoA mericanoD eE studio delL upus (GLADEL) cohort in 1997. This inception cohort recruited a total of 1480 multiethnic (Mestizo, African-Latin American (ALA), Caucasian and other) SLE patients diagnosed within two years from the time of enrollment from 34 Latin American centers with expertise in the diagnosis and management of this disease. In addition to the initial 2004 description of the cohort, GLADEL has contributed to improving our knowledge about the course and outcome of lupus in patients from this part of the Americas. The major findings from this cohort are highlighted in this review. They have had important clinical implications for the adequate care of SLE patients both in Latin America and worldwide where these patients may have emigrated.